Identifikasi Karakteristik, Kebutuhan, dan Minat Pengrajin Tempe (Studi Kasus di Kampung Tempe Kota Pekalongan) - Yuliando, Henry; Purwadi, Didik; Naziha, Thalia; Putri Pradita, Sintia; Ida Gunawati, Amalia; Kartika Dewi, Mutiara (JURNAL LITBANG KOTA PEKALONGAN, 2024)
Pekalongan City, which has more than 100 tempeh producers, is in Kuripan Kertoharjo Village, making this village known as "Tempeh Village" or “Kampung Tempe”. Thus, there is a lot of potential that can be developed in this sub-district. The large number of tempeh producers in Pekalongan City shows that this is the main source of income. Therefore, it is necessary to identify the characteristics of tempeh producers, the problems they face, and their needs. This research aims to identify the characteristics of tempeh producers in Kuripan Kertoharjo Village, including age, income, production capacity, length of time the business has been running, etc. Apart from that, this research also aims to find out the problems faced by tempeh producers, as well as the needs of tempeh producers so they can develop their businesses. Data collection was carried out through FGD interviews and questionnaires with 30 tempeh producers. Through this research, we can find out what aspects are obstacles for tempeh producers in running their business and can be used as a reference for Local Government Services regarding what can be done to develop Tempeh Village. Finally, in this research, we can find out the characteristics of tempeh producers in Tempeh Village, Pekalongan City which include age, business background, length of time the business has been running, daily soybean needs, marketing methods, and involvement in the community. Apart from that, we also know that the needs of tempeh producers are grouped into four aspects, namely training needs, groups or associations, activities in groups or associations, and development needs. Keywords: Characteristics identification, Kampung Tempe/Tempeh Village, Pekalongan City, tempeh producers,